El Camí de l'Acròpoli (1991)
Descripción material de los senderos que conducen a la Acropolis.
Keywords: PIKIONES, DEMETRES; ACROPOLIS; ATENAS; PERIFÉREIA PROTEVOÚSIS; GRECIA; INTERVENCIONES; PATRIMONIO; MONUMENTOS; SENDAS PEATONALES; CAMINOS; CONSTRUCCION; PIEDRA